Legal aspect of income tax collection from buying and sale transactions through social media - Siti Chairana Nurmecca (Central Research Institute for Agriculture (CeRIA), 2021)
This study aims to explain the reasons for entrepreneurs who earn income from buying and selling transactions through social media to collect income tax, discuss the mechanisms needed for the collection of income tax and discuss the rules that can be imposed for collecting income tax so that entrepreneurs who earn income from transactions in the media social is obligated to fulfill tax obligations like entrepreneurs in marketplaces and conventionally in creating a level playing field in running a trading business. The results of the study show that disparities/differences in arrangements for collecting income tax from e-commerce transactions are an obstacle to collecting taxes on income earned from buying and selling transactions through the electronic system (e-commerce), arrangements that only target entrepreneurs in the marketplace will cause a large shift -Most entrepreneurs in the market place to move to social media, because income tax is not collected on social media, so to deal with this, entrepreneurs who get income from buying and selling transactions through social media need to collect income tax to fulfill tax obligations according to income tax regulations. applies, so that there is no evasion and injustice in collecting taxes as a whole and thoroughly from online buying and selling transactions, in collecting income tax from buying and selling via social media cooperation between the directorate general of taxes and social media organizers is needed to obtain tax data in seeking state revenue , then the validity of the data is strengthened by the database contained in the national payment gateway (GPN) to detect the value of income transactions obtained from buying and selling transactions on social media, then the rules that can be imposed for income tax collection are following the same applicable income tax provisions like conventional entrepreneurs in general.